Rancang Bangun Aplikasi Administrasi Perkuliahan Pada Lembaga Pendidikan Pengembangan Profesi Indonesia (LP3I) Surabaya - Wicaksono, Faizal Try; Sulistiowati, Sulistiowati; Setyawan, Henry Bambang (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
LP3I is a non-formal educational institutions, LP3I Surabaya, which is the subsidiary of LP3I Jakarta. LP3I Surabaya was established in 1997 and located on the road Manyar Surabaya. LP3I Surabaya equivalent education Diploma II with a variety of majors. During this time, LP3I difficulty in recapitulation presence of students and lecturer as well as students academic grades. This is because the recapitulation is done one by one from lecturing activities report (LKP) and the attendance of lectures as much as 185 sheets. While recapitulation of students academic grades should be done by selecting one by one by the name of the student with the subjects that followed. Of the existing problems of administrative applications required courses that can help in the process of recapitulation of the presence of students and lecturer as well as students academic grades. Recapitulation of student attendance is used to determine the status of these students in exams, while the lecturers used to determine the presence of Wages (HR) faculty.Based on the results of trials that have been done, the application is successfully assist in the process of recapitulation. This journal discusses the outline of the administration application design lecture at the Institute of Education and Development (LP3I) Surabaya.